Commodification of Religion: Al-Jabbar Grand Mosque as a Religious Tourism Object in West Java - Mighfaza, M. Helmi; Shahruddin, Mohd Solahuddin (Jurnal Iman dan Spiritualitas, 2024)
This article discusses the Commodification of Religion at the Al-Jabbar Grand Mosque from the forms of commodification that exist at the Al-Jabbar Grand Mosque, as well as the impact of the commodification of religion for visitors and the community around the Al-Jabbar Grand Mosque. The research method used is a literature study by collecting data from various sources such as observation, field interviews, books, the internet and scientific journal articles. In its discussion, this article describes the forms of religious commodification that occur at the Al-Jabbar Grand Mosque, so that the Al-Jabbar Grand Mosque in the value of the Mosque's substance has a dual role and function as a house of worship. Then, this article also describes how the impacts that occur for visitors to the Al-Jabbar Grand Mosque and the impacts that occur with the surrounding community. This article concludes that the concept of religious commodification has a goal not to eliminate religious values, but religion responds and adapts to the development of an increasingly advanced era.